Marketing and library spaces, doomed to meet each other - Gallo-León, José-Pablo (Anuario ThinkEPI, 2017)
An approach to the marketing and promotion of library spaces is presented. While library marketing has been extensively studied, much like library design, few studies have been devoted to the marketing of physical spaces. This can be done in four ways: using marketing tools for library design; adapting the library´s spaces to improve the user experience; taking advantage of the presence of users to carry out market research; and using an architectural image to promote the library. Finally, the need to take care of the appearance and visual appeal of the library is presented.
Keywords: Library buildings; Library design; Marketing; Promotion.